Formação continuada de professores/as dos anos iniciais do ensino fundamental em matemática: uma revisão sistemática de artigos publicados nos últimos cinco anos - 2018 a 2023 - Vasconcelos, Driele Brasil (Universidade Federal de São Carlos, 2024)
The continuing education of teachers, when it comes to satisfaction research, appears increasingly discredited. Research shows that the ongoing teacher training currently offered is, for the most part, disconnected from the real needs of teachers and the teaching-learning process. Few continuing teacher training programs offered seek to overcome the gap: continuing teacher training and educational improvement for students. When analyzing the performance of Brazilian students in mathematics in national and international external assessments, it is noted that, with regard to mathematical proficiency, the national average achieved is significantly lower than the average performance achieved by dozens of other countries evaluated. Considering that current national and international research states that teacher training is directly related to student performance and impacts the quality of education, this bibliographical research – systematic review, developed in the Postgraduate Program in Education (PPGE) of the Federal University of São Carlos – UFSCar, São Carlos Campus, in the line of Research “School Education – Theories and Practices” had the general objective of analyzing national and international articles published in the last five years (2018-2023) on the bases of data from SciElo.org, Scopus and Web of Science with the theme “continuing training of teachers in the initial years of primary education in mathematics”, in order to identify how it has been approached and/or related to student learning/ to the. The study presents a rich collection of data and results, analyzed using a mixed approach and Bardin's (2016) content analysis techniques. The results showed that no Brazilian study developed in the last five years with the theme “continuing training of teachers in the initial years in mathematics” related and/or measured the impact of the continued training of teachers in the initial years in mathematics on the learning of students. We present a detail on how international articles measuring the impact of teachers' continuing education on student learning were structured and developed. The analyzes and results of this study can support future Brazilian research that may have this same intention. Future research can also explore spaces for dialogical training of teachers in the format of dialogical pedagogical gatherings aimed at teaching and learning the subject of mathematics in the early years of elementary school, incorporating the guidelines of recent national and international research, regulations and current national guidelines and reports from current international organizations.
Inservice teacher's education who teach mathematics in elementary school: a systematic review of articles published in the last five years - 2018 to 2023
Keywords: Formação continuada de professores; Desenvolvimento profissional do professor; Anos iniciais do ensino fundamental; Matemática; Inservice teacher education; Teacher’s professional development; Elementary school; Mathematics; CIENCIAS HUMANAS::EDUCACAO